Comparison of Chemical and UV Photo-Grafting Modification on Polyamide Microfiltration Membrane for the Preparation of Membrane Chromatography - Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Nurul Izwanie, Rasli (Asian J. Chem, 2016)
Membrane chromatography has been used widely as an alternative to the conventional packed bed chromatography for protein separation. Membrane chromatography used an adsorptive membrane that carried specific chromatography functionality. In the current study, a membrane chromatography was prepared by modification of commercial polyamide microfiltration membrane with acrylic acid monomer. Two modification methods were compared which are UV photo grafting and chemical grafting via redox reaction. Modification parameters studied were initiator concentration (1-50 mM), monomer concentration (0.2-5 M) and reaction time (5-60 min). The highest lysozyme binding capacity achieved was 0.175 mg of lysozyme/cm2 membrane for the membrane prepared via UV photo grafting using 10 mM of photo-initiator, 0.1 M of acrylic acid and 15 min of reaction time.